Effects of Ralgro Implants on Growth, Sexual Development, Carcass Characteristics, and Eating Quality of Bulls Implanted From Birth to Slaughter - J. R. Greathouse; M. C. Hunt; Michael E. Dikeman; L. R. Corah; Curtis Kastner; R. J. Pruitt (Kansas Agricultural Experiment Station Research Reports, 1982)
Growth, performance, sexual development, carcass characteristics, and eating quality were evaluated on 40 fall-born Angus bulls. Twenty of the bulls were implanted five times with Ralgro at an average interval of 106 days, beginning near birth. The other 20 bulls served as nonimplanted controls. Bull calves remained with their dams on native southeast Kansas pasture for an average of 320 days; they were then allotted to drylot pens (feedlot beginning) and placed on a 75% concentrate ration. Bulls from each treatment were fed to target weights of 1000 and 1100 pounds, and then slaughtered. Ralgro implanting increased average daily gain 6.6% over that of the controls from birth to the feedlot beginning, and 9.4% from the feedlot beginning to the first slaughter endpoint (196 days on feed). Feed efficiency was improved 8.2%, with implanting when the first group of implanted and control bulls were slaughtered (196 and 231 days on feed, respectively). Implanting reduced semen quality, reduced the number of bulls producing semen, and depressed the development of reproductive organs. Sex drive was unaffected by implanting. Implanting resulted in fatter carcasses and tended to increase yield grades, but did not affect final quality grades. Lean from control carcasses tended to be firmer and have a finer texture, but color was not affected by implanting. Loineye steaks from implanted bulls were significantly more tender, as judged by taste panel ratings and by Warner-Bratzler shear forces.
Keywords: beef cattle; implants; Ralgro; Compudose